RISĀLAH MENURUT KONSEPSI ALQURAN - Mukhlis Mukhtar (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: The word al-risālah is one of the words used in the Qur’an. The existence of al-risālah cannot be separated from the presence of the messenger of Allah among mankind in every age. That is because the messengers were given the recommendation directly by God to carry, to deliver and to teach al-risālah. Al-risālah carried, delivered and taught by the messengers to mankind contains the messages of the Almighty God to invite people not to worship God except Allah and regulate human life in relation to God, fellow humans and their environment. Kata Kunci: risalah, kosepsi Alquran, rasul